Fascia Iliaca Compartment Block for Femoral Bone Fractures in Prehospital Care. Issue 3 (1st May 2003) - Lopez, Sandrine; Gros, Thierry; Bernard, Nathalie; Plasse, Christian; Capdevila, Xavier
Abstract : Background and Objectives: The fascia iliaca compartment block provides a faster and more consistent simultaneous blockade of the lateral cutaneous and femoral nerves than the "3 in 1" block. We studied the effectiveness of this technique for analgesia after a femoral bone fracture in pre-hospital care. Methods: Patients with an isolated femoral shaft fracture were included. A fascia iliaca compartment block was performed on all of them. Twenty milliliters of lidocaine 1.5 % with epinephrine were injected under the fascia iliaca. The intensity of pain was measured using a simplified verbal scale (SVS) from 0 (no pain) to 4 (extreme pain). The SVS was noted before the block was performed, 10 minutes later, and then on admission to the trauma care center. Sensory blockade was evaluated using cold perception in the lateral, medial, and internal part of the thigh 10 minutes after block performance and on arrival at the trauma care center. Results: Twenty-seven patients were enrolled in this study. The SVS was 3 (3-4) before the block, 1 (0-2) 10 minutes after the block, and 0 (0-1) when arriving at the trauma care center ( P < .05). The SVS was lower when the internal part of the thigh was blocked. Conclusion: The fascia iliaca compartment block is a simple, inexpensive, and effective method of prehospital analgesia for femoral shaft fracture. A sensory block of the internal part of the thigh is an early predictive sign of optimal pain relief.